Prevalence and Impact of TPMT and NUDT15 Gene Polymorphisms on Consolidation Phase Chemotherapy in Pediatric ALL - S., Abhilasha; Mahantashetti, Niranjana; K., Hershavardhini; Doddannavar, Ashwini; Bafna, Vibha; Bartakke, Sandip (Indian Journal of Medical and Paediatric Oncology, 2025)
Acute lymphoblastic leukemia (ALL) is the most frequently occurring cancer in children, with cure rates exceeding 90%. The consolidation phase (CP) plays a vital role in lowering relapse rates. However, chemotherapy in this phase is commonly delayed due to toxicities related to 6-mercaptopurine (6-MP). The metabolism of 6-MP depends on enzymes encoded by the thiopurine S-methyltransferase (TPMT) and nucleoside diphosphate (NUDT15) (nudix hydrolase 15) genes. Inherited variations in these genes are known to impact drug metabolism, affecting effectiveness and toxicity.This study was conducted to determine the prevalence of notable TPMT and NUDT15 gene variants in pediatric patients with ALL from North Karnataka. It also aimed to evaluate the association of these polymorphisms with chemotherapy interruptions and related toxicities during the CP.This longitudinal analysis included 106 patients newly diagnosed with ALL. Genetic screening for TPMT and NUDT15 mutations was carried out before the initiation of treatment. Data collected included the total 6-MP dose administered during CP, the number of delayed treatment days, frequency of febrile neutropenia (FN) episodes, and their duration.Over a period of 2.5 years, 106 patients were enrolled. The male-to-female ratio was 1.52, and the average age was 7.19 ± 4.08 years. Variants in NUDT15 and TPMT were found in 24.5 and 3.77% of cases, respectively. Those with genetic mutations had an average CP delay of 13.5 days and experienced more FN episodes, with a statistically significant difference (p = 0.002).The frequency of TPMT and NUDT15 mutations in this group was higher than in previous Indian reports. These gene variants were linked to longer treatment delays and increased toxicity during CP. We propose that TPMT and NUDT polymorphism analysis should be performed upfront at diagnosis, so that consolidation delays can be minimized and toxicities can be reduced, which may improve the overall outcome.
Keywords: 6-MP toxicity; chemotherapy delay; consolidation phase; NUDT polymorphism; TPMT polymorphism